Kerne, Kooperation und Konkurrenz Kernforschung in Österreich im internationalen Kontext (1900-1950) - Fengler, Silke (2014)
At the end of the 19th and beginning of the 20th century, a new sub-field of physics and chemistry emerged centering on radioactivity. Its disciplinary structures were slow to crystallize. The early phase of this field was characterized by substantial international exchange between the European centers in Vienna, Paris, Berlin and Cambridge and a concomitant high degree of transdisciplinarity. Research on radioactivity was also marked by an unusual openness in respect to gender and gender politics. The volatile political and social context of nuclear research, which abruptly changed several times, acted to further, impede or block these initiatives to transcend diverse boundaries in science, politics, and society. The two central questions of the present project are: How did the agendas and foci of Austrian nuclear research, and the styles of work of the scientists, change within the framework of international cooperation and competition? How were these developments dynamically linked with the political, social and cultural shifts in European history in the 20th century? The historical analysis starts with the founding of the Vienna Institute for Radium Research (IRR), including the institutes for physics at the University of Vienna that worked in close cooperation with the IRR. The period under investigation extends from the late years of the Austrian-Hungarian Empire to World War I, the era of "Red Vienna," the "state of estates" (Ständestaat) and the Nazi dictatorship, down to the full restoration of Austrian sovereignty in 1955. The study will include systematic transnational comparisons with the other centers of European nuclear research, based in part on existing literature from the history of science, as well as exact reconstructions of the bilateral and multilateral cooperative links and relations with the international scientific community. In this way, the proposed project is expected to go beyond the historical reconstruction of nuclear research in Austria and shed light on the importance of nationality and internationality, both for framing politics and as mental and cultural points of reference for the behavior and actions of the scientific actors and the production of scientific knowledge under shifting constellations of war and peace, democracy and dictatorship.